Integrating clinical psychology and social care in oral cancer prevention & early detection: a needs assessment for interprofessional education - Sujir, Nanditha; Ahmed, Junaid; Anand Ramakrishna,; Ali Mohammed, Ciraj; Unnikrishnan, Bhaskaran; Gilbert, John H. V.; Gangadhara, Vasudha Kadikadka; Monteiro, Meena Juliet (Frontiers in Education, 2025)
BackgroundTo address the challenges in the early diagnosis and prevention of oral cancer, it is essential to include clinical psychology and social care professionals in interprofessional healthcare teams. In this context, a needs assessment study was conducted to inform the development of an interprofessional education and collaborative practice (IPECP) course focused on oral cancer for students in clinical psychology and social care. The objectives of this study were to develop a tool for assessing the knowledge, attitudes, and practices (KAPs) related to oral cancer prevention and early detection among these students and to evaluate the current KAP levels within this student cohort. Additional objectives were to estimate the likelihood that students would demonstrate strong KAP scores related to oral cancer prevention and early detection and to assess their readiness for interprofessional learning and collaborative practice.MethodsTwo questionnaires were employed in this study: (1) a custom-designed questionnaire was developed, validated, and administered to assess KAP related to the early detection and prevention of oral cancer and (2) the Readiness for Interprofessional Learning Scale (RIPLS). For data analysis, both descriptive and inferential statistical methods were applied. These included the Mann–Whitney U test, ordered logistic regression, and probit analysis. A significance level of p < 0.05 was set for all the statistical tests.ResultsA total of 220 clinical psychology students and 226 social care students were included in the study. The mean scores related to KAP were 11.04 ± 1.782, 5.28 ± 1.292, and 4.56 ± 1.583, respectively, and the mean score for RIPLS was 82.23 ± 10.961 among clinical psychology students. Among the social care students, the KAPs were 10.46 ± 2.688, 5.36 ± 1.626, and 5.86 ± 1.806, respectively, and the mean RIPLS score was 46.58 ± 9.705.ConclusionThe analysis revealed that both the clinical psychology and social care student cohorts presented low scores in knowledge and practices related to the prevention and early detection of oral cancer. However, the Readiness for Interprofessional Learning Scale (RIPLS) results indicated a more positive attitude toward interprofessional learning among clinical psychology students than among their social care counterparts.